2011
DOI: 10.1016/j.ejcts.2011.05.050
|View full text |Cite
|
Sign up to set email alerts
|

Adenosquamous carcinoma of the lung: surgical results as compared with squamous cell and adenocarcinoma cases

Abstract: ASC of the lung is more aggressive than AC and SC. The decreased survival of patients with ASC as compared with either of those single histology tumors suggests the need for a clinical trial of adjuvant chemotherapy that includes early-stage patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
69
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 13 publications
4
69
2
Order By: Relevance
“…1 Within NSCLC, adenocarcinoma (ADC) and squamous cell carcinoma (SCC) are the two major subtypes, with distinct prognoses and therapeutic remedies. 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…1 Within NSCLC, adenocarcinoma (ADC) and squamous cell carcinoma (SCC) are the two major subtypes, with distinct prognoses and therapeutic remedies. 2,3 …”
Section: Introductionmentioning
confidence: 99%
“…Although the symptoms of ASC are similar to those of other histological subtypes of NSCLC (7), aggressive characteristics including early metastasis, invasiveness, rapid growth and poor prognosis have been recognized (8)(9)(10). Consequently, valuable prognostic factors are urgently needed for patients with ASC.…”
Section: Introductionmentioning
confidence: 99%
“…ASC accounts for 0.4% to 4% of all lung cancers and thus is considered a relatively rare histologic subtype. ASC is substantially more aggressive than AC and SCC 2–8 . A previous study has shown that the 3‐ and 5‐year survival rates of patients with stage I ASC were similar to those of patients with stage IIIA AC or SCC 2 …”
Section: Introductionmentioning
confidence: 98%